Did Job Satisfaction and Organizational Commitment Reinforce Hospital Employees Organizational Citizenship Behaviour During Covid-19 Pandemic? - Iyus Rustandi; Abdul Rosid; Deswara Deswara; Dini Riani (International Journal of Artificial Intelligence Research, 2022)
The purpose of this study was to analyze the relationship between the variable Job Satisfaction and Organizational Citizenship Behavior and to analyze the relationship between the variables Organizational Commitment and Organizational Citizenship Behavior among hospital employees; during the covid-19 pandemic. This study uses a quantitative survey method, the respondents of this study were 350 hospital employees in Jakarta who were selected by simple random sampling method. Data analysis used Structural Equation Modeling (SEM) with SmartPLS 3.0 software as a tool. The data of this research was obtained by distributing online questionnaires which were distributed through social media. The conclusion of this study is that job satisfaction partially has a positive and significant effect on Organizational Citizenship Behavior, organizational commitment has a positive and significant effect on Organizational Citizenship Behavior.